Evaluation of a peer-support, 'mentor mother' program in Gaza, Mozambique; a qualitative study - Leila Katirayi; Sozinho Ndima; Amgad Farah; Whitney Ludwig; Atanásio Mabote; Ismail Chiposse; Ana Muteerwa; Jessica Greenberg Cowan; Ivete Meque (BMC, 2024)
Abstract Background Retention in prevention of mother-to-child transmission of HIV programs is critical to reduce vertical transmission. To addresses challenges with retention, Mozambique launched a peer-support program in 2018, in which HIV-positive mothers provide adherence support as mentor mothers (MMs) for HIV-positive pregnant and lactating women and HIV-exposed and infected children. Methods A descriptive qualitative evaluation was conducted across nine facilities in Gaza Province to assess the acceptability and barriers to implementation of the mentor mother program (MMP) among those receiving services and providing services. In-depth interviews and focus group discussions were conducted with MMs, MM supervisors, health care workers (HCWs), HIV-positive mothers enrolled in the MMP, HIV-positive mothers who declined MMP enrollment, and key informants involved in the implementation of the program. Thematic analysis identified emerging recurrent themes and patterns across the participants' responses. Data were collected between November-December 2020. Results There were initial challenges with acceptability of the MMP, especially regarding confidentiality concerns and MM roles. Sharing additional information about MMs and making small changes during the beginning of the MMP resulted in generally high acceptance of the MMP. HIV-positive mothers reported that counseling from MMs improved their understanding of the importance of anti-retroviral treatment (ART) and how to take and administer ART. HIV-positive mothers reported having reduced guilt and shame about their HIV-status, feeling less alone, and having more control over their health. MMs shared that their work made them feel valued and decreased their self-stigmatization. However, MMs also reported feeling that they had inadequate resources to perform optimal job functions; they listed inadequate transportation, insufficient stipends, and false addresses of clients among their constraints. Overall, HCWs felt that their workload was significantly reduced with MM support and wanted more MMs in the community and health facility. Conclusions This study found that the MMP was considered a substantive and highly valued support to HIV-positive mothers, resulting in increased ART literacy among patients, improved self-reported well-being and sense of community and reduced feelings of isolation. Recommendations include strengthening MM training, increasing financial and materiel resources, additional information provided to newly enrolled mothers and support for the male partners.